P830 Adherent-invasive Escherichia coli in inflammatory bowel disease impacts faecal microbiota transplantation efficacy by hindering engraftment of beneficial bacteria. (25th January 2019) - Xu, Z; Yang, K; Zhang, J; Zuo, T; Chevarin, C; Wong, S H; Chan, F K; Sung, J J; Yu, J; Barnich, N; Ng, S C
Abstract: Background: Adherent invasive Escherichia Coli (AIEC) invades gut epithelium and colonise the mucosa of patients with Crohn's disease (CD). Despite increasing use of faecal microbiota transplantation (FMT) to treat inflammatory bowel disease (IBD), mechanisms and factors affecting treatment outcome is unclear. This study aims to assess whether AIEC affects efficacy of FMT and explore underlying mechanisms of FMT success. Methods: C57BL/6 wild-type mice were colonised with an AIEC strain (AIEC62d; 109 CFU) recently isolated from the mucosa of a patient with Crohn's disease in Hong Kong or non-pathogenic E. coli strain (K12) ( n = 24/group). After 7 days of 2% DSS treatment, we switched to clean drinking water and gavaged these mice with faecal solution from healthy mice for three consecutive days. After a 7-day recovery period, we sacrificed all mice and assessed the length and histology score of the colon. Faecal AIEC load (CFU/mg) were quantified by plating on LB agar plate supplemented with 100 μg/ml ampicillin. Fluorescence in situ hybridisation (FISH) was performed to locate AIEC in the mouse gut. Colonic myeloperoxidase (MPO) and faecal lipocalin-2 (Lcn-2) (on going) were measured to assess the severity of colitis. Faeces were collected before and after FMT for 16s rRNA sequencing to analyse gut microbiota. Results: FMT transiently reduced faecal AIEC load compared with the no FMT group, but faecal AIEC load increased again at the end of FMT treatment and reached the same level as the no FMT group by Day 14. FISH staining showed remaining AIEC inside the epithelial cells of mouse colon after FMT treatment. After FMT, K12-colonised mice, but not AIEC-infected mice, showed ameliorated colitis, as indicated by body weight gain, elongated colon, and improved colonic histology. Alpha diversity (Shannon diversity index) in AIEC-infected mice was significantly lower than K12-colonised mice before FMT. FMT increased microbial diversity in K12-colonised mice but not in AIEC-infected mice. The proportion of donor derived microbes in K12-colonised mice was significantly larger than in AIEC-infected mice. Several taxa including Faecalibacterium prausnitzii, Akkermansia muciniphila, and the genus Allobaculum (related to health) were successfully engrafted in K12-colonised mice but not in AIEC-infected mice. Conclusions: This is the first study reporting that the presence of a microorganism (e.g. AIEC) by itself was sufficient to compromise the efficacy of FMT by hindering the engraftment of beneficial bacteria, leading to incomplete recovery of intestinal inflammation. Future FMT practice in IBD should consider patient stratification based on AIEC presence and their effects on FMT outcomes.